Psychological Issues Encountered By Students In Learning English Within The Pesantren Environment - Nashihin, Muhammad; Shofi Zuhri, Moh; Kavin Lidinillah, Moh (Institut Agama Islam Tarbiyatut Tholabah, 2024)
The prominence of the English language in various global domains has positioned it as the most dominant international language. However, learning English, especially within Islamic boarding schools (